Bagaimana Komitmen dan Motivasi berperan dalam Jenjang Karier Pegawai Biro Umum Setda Provinsi NTT? - Hasmin, Maria Osinta; Paridy, Anggraeny; Lopes Amaral, Maria Augustin (Research and Development Agency Ministry of Home Affairs, 2022)
Commitment, motivation, and performance are several factors influencing career path development. This research was conducted based on observations and preliminary data from pre-research results at the General Bureau of the Regional Secretary of East Nusa Tenggara Province, that employee commitment and motivation were still lacking. As a result, performance achievement and employee career paths decline. This study aims to prove and analyze the variables of Commitment and motivation on performance and their implications for career paths at the Secretary-General Bureau of East Nusa Tenggara Province. The population in this study were employees of the General Bureau of the Regional Secretary of the Province of NTT, as many as 115 people. The number of 90 samples in this study was determined from the number of indicators used, namely 18, multiplied by 5. Hence, the sample in this study was 90 respondents using the purposive sampling technique. The results of the descriptive analysis showed that the variables of Commitment, motivation, employee career path, and performance were included in the very good category. The results of inferential statistical analysis from the data from the General Secretariat of the Regional Secretariat of the Province of East Nusa Tenggara show that: 1). motivation and performance have a significant effect on employee career paths. 2). Commitment and motivation have a significant effect on performance. 3). Commitment does not significantly affect employee career paths; 4). Performance mediates the effect of Commitment and motivation on employee career paths; 4). Performance mediates the effect of Commitment and motivation on employee career paths. The contribution of the variables of Commitment, motivation, and performance to the career path of employees is 89.8 percent. At the same time, the rest is a contribution from other variables that do not contribute. It is recommended that the General Bureau of the Regional Secretary of East Nusa Tenggara Province increase Commitment and motivation for employees through creating comfortable and harmonious conditions in the work environment, giving prizes to employees who achieve targets, and providing periodic training.